Legal Regulation of Electronic Contract and General Review - Edisherashvil, Tea (European Scientific Journal, ESJ, 2017)
New informational era requires innovative approach to old problems (2). The mankind has entered a new phase of civilization development in XXI century. We live in the information technologies ongoing progress and the so called internet expansion era (3). Nowadays, informational awareness of society has reached the level that we hardly may imagine the fieldwhere information and communicational technologies are not applied to some extent. Information and communication technologies constitute quite a significant factor of influence onto society in the twenty-first century. Their innovative influence is related to people’s lifestyle, their education and work as well as interrelation between government and civil society. “Information and communication technologies have becoming quickly a stimulus of the vital importance for global economics development” - this is how the Global Informational Society Okinawa Charter starts provisions of which are dedicated to economic and social transformation incitation through information and communication technologies. The President the largest company of information technologies Cisco Systems Inc John Chambers states that “the scales of the outcomes of the social union revolution may supposedly exceed the industrial revolution; it equals conditions and creates unprecedented opportunities for countries, companies and individuals all over the world. Its outcomes may be economics success and survival basic factors of which are response velocity and changeability skills, but not size, geographical location or material resources (5). An electronic contract constitutes a transaction executed in the electronic form which does not apply a written form of any kind except the electronic one and which is signed electronically. For example, if you send such a contract to your business partner who signs it electronically and returns to you, such a contract is valid. An electronic contract may exist in the so called “click-toaccept” form which is mainly applied in relation to programs to be uploaded. In this case a user presses “I Agree“ button and a contract is executed (6).